SURVIVAL ANALYSIS WITH WEIBULL REGRESSION ON THE RATE OF HEALING OF DIABETES MELLITUS PATIENTS - Widya Wahyu Cahyani; Fibri Rakhmawati (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
Survival analysis is a statistical technique used to study survival related to time, starting from the initial time of the study that has been determined until the end time of the study, therefore the purpose of this study was to determine the equation of the Weibull regression model of the clinical condition of patients with diabetes mellitus at the Malahayati Islamic Hospital Medan and what factors affect the rate of recovery of the clinical condition of patients with diabetes mellitus. The type of research used in this paper is Applied Research, from data collection and analysis, the results are obtained based on the Kaplan-Meier curve, visually it can be seen that the longer the coronary heart disease patient recovers (t). the less likely they are not to recover until time t. The Kolmogorov-Smirnov test was used to test the Weibull distribution, which describes the survival time of patients with diabetes mellitus. The partial test results indicate that the variables of gender, age, hyperglycemia, hypertension, and complications significantly impact the model. The following is how the Weibull regression model for the recovery time data of patients with diabetes mellitus was acquired for this study: S (t|x) = exp (-exp (1.42219+ (-0.01018)x1 + 0.03942x2 + (-0.02976)x3 + (-0.01887)x4 ) t ) α